2021
DOI: 10.1126/science.abe6230
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided multivalent nanobodies block SARS-CoV-2 infection and suppress mutational escape

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic continues to spread with devastating consequences. For passive immunization efforts, nanobodies have size and cost advantages over conventional antibodies. Here, we generated four neutralizing nanobodies that target the receptor-binding domain of the SARS-CoV-2 spike protein. We defined two distinct binding epitopes using x-ray crystallography and cryo-electron microscopy. Based on the structures, we engineered multivalent nanobodies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
464
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 351 publications
(489 citation statements)
references
References 75 publications
24
464
0
1
Order By: Relevance
“…Recent reports on SARS-CoV-2 mutations in both human and mink populations give rise to concerns about viral escape from current vaccines and therapeutics in development (Andreano et al, 2020; Greaney et al, 2021a; Kemp et al, 2021; Mallapaty, 2020; Oude Munnink et al, 2021; Tegally et al, 2020; Voloch et al, 2020). However, antibody cocktails that bind to distinct epitopes can increase neutralization breadth and may help prevent escape mutations (Baum et al, 2020; Du et al, 2020; Greaney et al, 2021b; Hansen et al, 2020; Koenig et al, 2021). We previously reported that CV38-142 does not compete for RBD binding with other potent antibodies in our sample set, which are encoded by diverse germline genes, such as CV07-200 (IGHV1-2), CV07-209 (IGHV3-11), CV07-222 (IGHV1-2), CV07-250 (IGHV1-18), CV07-262 (IGHV1-2), CV38-113 (IGHV3-53), and CV38-183 (IGHV3-53) (Kreye et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports on SARS-CoV-2 mutations in both human and mink populations give rise to concerns about viral escape from current vaccines and therapeutics in development (Andreano et al, 2020; Greaney et al, 2021a; Kemp et al, 2021; Mallapaty, 2020; Oude Munnink et al, 2021; Tegally et al, 2020; Voloch et al, 2020). However, antibody cocktails that bind to distinct epitopes can increase neutralization breadth and may help prevent escape mutations (Baum et al, 2020; Du et al, 2020; Greaney et al, 2021b; Hansen et al, 2020; Koenig et al, 2021). We previously reported that CV38-142 does not compete for RBD binding with other potent antibodies in our sample set, which are encoded by diverse germline genes, such as CV07-200 (IGHV1-2), CV07-209 (IGHV3-11), CV07-222 (IGHV1-2), CV07-250 (IGHV1-18), CV07-262 (IGHV1-2), CV38-113 (IGHV3-53), and CV38-183 (IGHV3-53) (Kreye et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Viruses employ numerous strategies to evade CD8 + T cell immune responses (40)(41)(42). The SARS-CoV-2 encoded ORF8 protein is hypothesized to down-regulate the surface expression of MHC-I molecules (43), and several reports linked mutations within the viral spike protein to the evasion of neutralizing antibody responses (28)(29)(30)). Yet, we still lack a comprehensive understanding of the intrinsic capabilities of SARS-CoV-2 for immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evolutionary evidence for CTL-mediated control of RNA viruses causing chronic infections like HIV and HCV is provided by mutations occurring in viral epitopes CORONAVIRUS SARS-CoV-2 mutations in MHC-I-restricted epitopes evade CD8 + T cell responses which directly interfere with MHC-I-restricted T cell antigen recognition and killing by CTLs (24)(25)(26)(27). While several mutations in SARS-CoV-2 have recently been associated with an escape from antibody responses (28)(29)(30), the extent to which SARS-CoV-2 mutations may upend the presentation of virusderived peptides via MHC-I remains to be determined. In this study, we used deep viral genome sequencing to identify nonsynonymous mutations in previously reported MHC-I epitopes.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, antibody fragments, especially camelid V H H single-domain antibodies, or nanobodies have also been successfully developed for virus neutralization [5][6][7][8][9][10][11][12] . Compared to mAbs, nanobodies (Nbs) are substantially smaller (~ 15 kDa) yet can still bind virus antigens with excellent specificity.…”
Section: Introductionmentioning
confidence: 99%